The Influence of Family Parenting Patterns for Women Factory Workers on Moral Education in RW 04 Ketitang Village, Nogosari District, Boyolali Regency - Fira Nisa Rahmawati (BUANA GENDER : Jurnal Studi Gender dan Anak, 2022)
This study aims to examine the effect of female factory worker parenting on children's moral education in RW 04 Ketitang Village, Kec. Nogosari Kab. Boyolali. This study is a quantitative study using a sample of 39 mothers who work as factory workers. This research can be concluded that the parenting style of the family of factory workers has a significant influence on the moral education of children in RW 04 Ketitang Village, Kec. Nogosari Kab. Boyolali. Correlation between family upbringing of factory workers and children's moral education. The correlation value obtained is 0.711. This means that the correlation between the family upbringing of women factory workers and the moral education of children in RW 04 Ketitang Village, Kec. Nogosari Kab. Boyolali is 0.711, this can be interpreted as a strong and significant relationship. While the results of the coefficient of determination (r2) = 50.5% while the remaining 49.5% is influenced by other variables that are not included in this study. These variables, for example, are due to internal factors, namely factors from humans themselves including instincts, habits, and heredity. Or because of external factors such as community environment, friends, and so forth.